(untitled) - D W Norman (Rome, 1995)
This manual is based on the experiences of the authors over the last two decades. Much of the documentations of these experiences has occurred over the last five years with the production of three sets of documents on the methodology for undertaking the farming systems research approach. These were as follow: * The production of a farming system research manual for Botswana. * A series of lectures given at Mahalapye Rural Training Centre, Botswana, 1992. * A series of lectures given as part of a Sustainable Farming Systems Course at the Swedish University of Agricultural Sciences.
Keywords: farm management